PELAKSANAAN PENGAWASAN PADA KANTOR YAYASAN IGASAR SEMEN PADANG - DINDA ULFA KAMARANI (Jurnal Bahana Manajemen Pendidikan, 2016)
The fact in the field indicate that the controlling at the Yayasan Igasar Semen Padang office has not been maximal. The purpouse of this research is to get information about controlling at the Yayasan Igasar Semen Padang office. This research is descriptive. Population in this research is the all employees that there is in the Yayasan Igasar Semen Padang office, who is numbered 40 peoples and the sample are 36 peoples. Those are taken by using Kretjie table and quota sampling technique. The instrument of this research is questioner with Likert scale model that has been tested for validity and reliability. The data analyze through percentage. The result of this research is the controlling at Yayasan Igasar Semen Padang office that enough category with percentage score 70%.